Improved Bond Strength Performance of Geopolymer Mortars: Role of High Volume Ground Blast Furnace Slag, Fly Ash, and Palm Oil Fuel Ash Incorporation - Huseien G.F.; Hussein Z.J.; Kubba Z.; Mikhail Nikolaevich B.; Mirza J. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Alkali-activated binders have become popular in the construction industry for their eco-friendly attributes. Various wastes from industries and agricultural sectors containing high concentrations of aluminosilicate and calcium oxides can be used to design these binders. This study evaluated the effect of high-volume granulated blast furnace slag, fly ash, and palm oil fuel ash additions on the bond strength performance of the proposed geopolymer mortars. Various levels of slag (50, 60, and 70%) and fly ash were substituted by palm oil fuel ash to determine the impact of SiO2:Al2O3, CaO:SiO2, and CaO:Al2O3 and their proportions on the geopolymerization process and the strength performance of the designed mortars. The bond strength performance of the mortars was assessed in terms of slant shear, flexural, and splitting tensile strength tests. The mineral properties of the designed mortars were obtained using X-ray diffraction, scanning electron microscopy, and Fourier transform infrared measurements. The incorporation of fly ash and palm oil fuel ash in the mortars caused a considerable decrease in the CaO:SiO2 and CaO:Al2O3 ratios, thus reducing the geopolymerization process and strength performance. The reduction in slag from 70% to 50% was counterbalanced by the increasing content of fly ash and palm oil fuel ash, which led to a drop in the compressive strength from 97 MPa to 56 MPa. In each level of slag, the replacement of fly ash by up to 10% palm oil fuel ash added more loss in strength values. In addition, the surface morphology of prepared mortars with lower palm oil fuel ash content was significantly enhanced, indicating the presence of less porosity and unreacted particles. The achieved mortars were asserted to be extremely well matched with the concrete substrates, offering effective binders for widespread construction uses. 2023 by the authors.